Pengaruh Bentuk Perlakuan Orang Tua Terhadap Emosi Negatif Remaja di Kelurahan Tanah Sirah Kecamatan Lubuk Begalung Padang - Sari, Miya Lhofita; Kasih, Fitria; Alfaiz, Alfaiz (Bimbingan dan Konseling, 2014)
Something which is very much causing negative emotion is about social problems such as, relation with parents, teacher and friends. Parents often treat teenager like child which is not given oppurtunity to be theirself in taking decision about their life. The purpose of this research is to express and describe: 1) Profile of authoritian parents treatment, 2) Profile of authoritative parents treatment, 3) Profile of negative emotion teenagers, 4) The effect of authoritarian parents treatment toward negative emotion for teenagers, 5) The effect of authoritative parents treatment toward negative emotion for teenagers. The research uses Descriptive-Correlational Research. The population of this research is all of teenagers in RW 05 and RW 07 Kelurahan Tanah Sirah Kecamatan Lubuk Begalung Padang. The sample of this research is 75 person by using Area Sampling Technique. To analysis of data is used Product Moment Correlation Coefisien Karl Perason Formula, then compare with the value table r product moment, after that is done calculation examination t and compare the result of calculation with the value table distribution t. The result of this research is determined that there are significant effects between authoritarian of parents treatment toward negative emotion teenagers where tcalculationâ¥ttable (4,583â¥1,99) with sig 0,05. Thus, there are significant effect between authoritative of parents treatment and negative emotion teenagers where tcalculationâ¥ttable (2,614â¥1,99) with sig 0,05. Based on the result of research, the researcher suggests teenagers that can adapt parents treatment toward negative emotion. In addition, parents can give good treatments, not only authoritative parents is good based the theories, but also in the field, the teenager can keep care with their friends. In briefly, authoritative treatments give effect of negative emotion for teenagers only 8,6% and others.